Pacientes com acidente vascular cerebral : validação de definições constitutivas e operacionais construídas para o resultado de enfermagem mobilidade - Moreira, Rafaella Pessoa (2011)
The study aimed at identifying and validating the constitutive and operational definitions of the mobility outcome and its indicators present in the Nursing Outcomes Classification (NOC 2010). The study was of methodology type and was performed in three stages: concept analysis, validation by specialists and clinical validation of the instrument. For the selection of productions it was used the online access to five databases: Scopus, PubMed, Cinahl, Lilacs and Cochrane, with the descriptors: mobility, stroke, nursing and their synonyms in both Portuguese and Spanish languages. 1521 articles were identified in all the databases searched and a careful selection resulted in 49 articles. Amongst the fifteen different countries, we highlight the articles published in Canada (26.7%), especially works from 2001 (95.9%) by physiotherapists (34.6%) in rehabilitation units (61.5 %). The attributes identified for Mobility were: walking, standing, sitting, placing the leg side to side, turning around, start and stop walking, climbing stairs, motor function, transfer and motor skill. For Mobility limitation: hemiplegia, hemiparesis, gait deficit and decreased motor skills. It was also created a sample case and an opposite case and were identified antecedents and consequences for both terms Mobility and Mobility limitation. After the concept analysis stage, it was brought forward an instrument with the constitutive and operational definitions for the indicators of the Mobility outcome by using the principles of psychometrics. This instrument was assessed by 23 specialist nurses who met the criteria adapted from Fehring (1994). The data were compiled into a spreadsheet program Microsoft Office Excel 2007 and analyzed by SPSS version 16.0. Most specialists was female (95.7%), worked in the State of Ceará (76.0%) in institution of higher education and hospitals (56.5%), was a master (78.3%) and had experience working with mobility and / or stroke. It was noted that the following indicators: Run, Jump, Crawl and Movements performed with ease showed ratios statistically less than 85% for most of the psychometrics criteria. Moreover, most of the nurses suggested the removal of these indicators by judging they were not representative for patients who had strokes. Thus, these indicators were excluded when defining the instrument to be applied in the clinical validation of the instrument stage. The data collection for the third stage took place in the neurology first-aid room of a referral hospital for treatment of patients with stroke in Ceará State and all ethical aspects have been followed at all stages of the study. After the researcher of the study confirmed the existence of the Impaired physical mobility nursing diagnosis in patients who had stroke, a pair of nurses applied the instrument with the constitutive and operational definitions identified and validated in the first two stages of the study while another pair used the same instrument without the definitions. As for the analysis of the nurses evaluations, there was similarity amongst the pair of evaluators who used the instrument with the constitutive and operational definitions for all indicators and amongst the pair who used the instrument without these definitions in applying the statistical tests from Fridman and the Intraclass Correlation Coefficient. With the use of this coefficient to such indicators: Balance, Walking, Joint movement and Body positioning performance, it was found a higher correlation between the evaluators who used the definitions as compared to those who did not. As for the following indicators: Gait, Muscle movement, Performance in the transfer and coordination, the agreement was higher amongst the nurses who did not adopt the definitions. But overall, it was observed that for most indicators there was greater agreement amongst the pair who used the instrument with the constitutive and operational definitions. However, it is recommended to execute other validation researches with the Mobility nursing outcome in patients with stroke and in several other clinical situations as well. This research may contribute to the improvement of the NOC taxonomy.